On topologies over rings - Syed M. Fakhruddin (International Journal of Mathematics and Mathematical Sciences)
In this note, we show that if a topology F¯ over a ring A satisfies a certain finiteness condition, then the Gabriel topology G¯ generated by F¯ can be explicitly constructed and it also satisfies the same finiteness condition.